The Cognitive Benefits of Educational Games in Al Qur'an Learning for Young Learners at Madrasah Ibtidaiyah - Rusdiana Husaini; Muqarramah Sulaiman Kurdi; Musyarrafah Sulaiman Kurdi (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2023)
This library research presents a comprehensive review of literature on the cognitive benefits of educational games that can be implemented in Al Qur'an learning for young learners at Madrasah Ibtidaiyah. The study explores the significance and multifaceted nature of these benefits, focusing on various cognitive processes and mechanisms involved in game-based learning. This study employs the library research methodology to comprehensively describe the cognitive benefits of educational games in Al Qur'an learning for young learners at Madrasah Ibtidaiyah. The approach involves a systematic descriptive analysis to explain the obtained facts. Analyzing existing literature provides a broad understanding of educational games in Al Qur'an learning for young learners and informs future empirical studies in this area. The findings reveal that educational games enhance cognitive development in young students through several key factors. These factors include promoting active engagement, providing scaffolding to support learning, facilitating authentic application of cognitive skills, reinforcing learning through repetition, fostering critical thinking, offering feedback and rewards, facilitating problem decomposition and strategy development, promoting collaborative learning, and enabling a state of flow. By leveraging these cognitive processes and mechanisms, educational games offer an interactive, engaging, and effective approach to Al Qur'an learning. The integration of game elements captures the attention and interest of young learners, fostering deep and meaningful engagement with the subject matter. The research emphasizes the importance of incorporating educational games as a valuable tool in Al Qur'an education for young learners at Madrasah Ibtidaiyah.